Deadweight costs and optimal capital structure. - Liang, Huijun. (2011)
In this paper, we explore the incoporation of deadweight costs in the restructuring process for multinational corporations (henceforth, MNCs) and develop the following theory: A MNC will not completely avoid renegotiation in a country where deadweight costs is prevalent. This theory suggests why having adopted a complete mix of parent and subsidiary debt financing, MNCs will choose to renegotiate with both the parent and subsidiary creditors in an event of financial distress. Banerjee and Noe (2010) shows that MNCs do not necessarily obtain all of their financing in locations that feature the most creditor friendly legal regime. In this paper, our model is consistent with those empirical findings. However, we shall go deeper in exploring how the presence of deadweight costs affect a MNC’s (1) optimal capital structure, and (2) optimal renegotiation strategy. The proposed model in this paper shall provide empirical findings on the amount of debt allocated in both the parent and subsidiary countries, as well as the value of deadweight cost for which the optimal renegotiation strategy changes.